Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1a,P=\left(x+2\right)^3+\left(x-2\right)^3-2x\left(x^2+12\right).\)
\(=x^3+6x^2+12x+8+x^3-6x^2+12x-8-2x^3-24=0\)
\(b,Q=\left(x-1\right)^3-\left(x+1\right)^3+6\left(x+1\right)\left(x-1\right)\)
\(=x^3-3x^2+3x-1-x^3-3x^2-3x-1+6\left(x^2-1\right)\)
\(=-6x^2-2+6x^2-6=-8\)
3) \(x^2-7x+6=0\)
\(\Leftrightarrow x^2-6x-x+6=0\)
\(\Leftrightarrow x\left(x-6\right)-\left(x-6\right)=0\)
\(\Leftrightarrow\left(x-6\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-6=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=6\\x=1\end{matrix}\right.\)
S=\(\left\{6;1\right\}\)
\(\)
Rút gọn các phân thức:
a) \(\frac{\left(3x+2\right)^2-\left(x+2\right)^2}{x^3-x^2}=\frac{9x^2+12x+4-x^2-4x-4}{x^3-x^2}=\frac{8x^2+8x}{x^3-x^2}=\frac{8x\left(x+1\right)}{x^2\left(x-1\right)}=\frac{8\left(x+1\right)}{x-1}\)
b) \(\frac{x^4-1}{x^3+2x^2-x-2}=\frac{\left(x^2-1\right)\left(x^2+1\right)}{\left(x^3-x\right)+\left(2x^2-2\right)}=\frac{\left(x^2-1\right)\left(x^2+1\right)}{\left(x+2\right)\left(x^2-1\right)}=\frac{x^2+1}{x+2}\)
c) \(\frac{x^2+7x+12}{x^2+5x+6}=\frac{\left(x^2+3x\right)+\left(4x+12\right)}{\left(x^2+3x\right)+\left(2x+6\right)}=\frac{\left(x+3\right)\left(x+4\right)}{\left(x++3\right)\left(x+2\right)}=\frac{x+4}{x+2}\)
d) \(\frac{x^{10}-x^8+x^6-x^4+x^2-1}{x^4-1}=\frac{\left(x^{10}-x^8\right)+\left(x^6-x^4\right)+\left(x^2-1\right)}{\left(x^2-1\right)\left(x^2+1\right)}=\frac{\left(x^2-1\right)\left(x^8+x^4+1\right)}{\left(x^2-1\right)\left(x^2+1\right)}=\frac{x^8+x^4+1}{x^2+1}\)
\(\Leftrightarrow\frac{7\left(x-2\right)^2}{84}-\frac{4\left(x+1\right)^2}{84}=\frac{3\left(x-4\right)\left(x-6\right)}{84}\)
\(\Leftrightarrow7\left(x-2\right)^2-4\left(x+1\right)^2=3\left(x-4\right)\left(x-6\right)\)
\(\Leftrightarrow7\left(x^2-4x+4\right)-4\left(x^2+2x+1\right)=3\left(x^2-10x+24\right)\)
\(\Leftrightarrow7x^2-28x+28-4x^2-8x-4=3x^2-30x+72\)
\(\Leftrightarrow7x^2-28x+28x-4x^2-8x-4-3x^2+30x-72=0\)
\(\Leftrightarrow-6x-48=0\)
\(\Leftrightarrow-6x=48\)
\(\Leftrightarrow x=-8\)
Vậy tập nghiệm của pt là \(S=\left\{-8\right\}\)